COMPARATIVE EVALUATION OF SELECTED POLYMERS AND PLASTICIZER ON TRANSDERMAL DRUG DELIVERY SYSTEM - Sethi, Bhawana; Mazumder, Rupa (International Journal of Applied Pharmaceutics, 2018)
Objective: The present work was aimed at preparation of transdermal patches by a solvent casting method using a varying concentration of polymers i.e. methocel (K15 and K100), ethocel (4 and 10), gelatin, chitosan, eudragit (RL and RS) grade using plasticizer (glycerin and propylene glycol). Methods: The ratio of drug to polymers and plasticizer was varied and the effect of formulation variables was studied. Prepared transdermal patches were evaluated for physicochemical properties, in-vitro permeation studies, content uniformity, primary skin irritation studies and FT-IR studies. Results: The formulated transdermal patch by using Methocel K 100 M showed good physical properties. The average weight of patches prepared using glycerin as a plasticizer were ranged from 42.33-67.00 mg and propylene glycol as a plasticizer were ranged from 40.67-67.67 mg. The percentage moisture absorption varies from 1.76 to 10.73 for patches formulated using glycerin and 2.28 to 7.97 for propylene glycol patches. The percentage moisture loss from patches prepared using glycerin was ranged from 2.75 to 11.54 and 2.87 to 12.02 from propylene glycol. The water vapour transmission rate from patches prepared using glycerin was ranged from 0.25 to 0.92 and 0.41 to 1.76. The formulated patch showed the acceptable quantity of medicament ranged from (100.20-101.05%). This result met the test content uniformity as per BP (85% to 115%). According to that, the drug was consistent throughout the patches. The formulation PGD is considered as the best formulation, since it shows a maximum in vitro drug release as 43.75 % at 24 h. The drug release kinetics studied showed that the majority of formulations was following zero order. Conclusion: In conclusion, controlled release transdermal drug delivery system patches of aliskiren can be prepared using polymer combinations, with a different plasticizer. The release rate of drug depends upon the polymer. However, release kinetics followed zero order.